Andar per indici: Petrarca e l'ordine del libro di lettere (Quaderni di Gargnano, 2018)
The essay considers the chronological order in which the ancient manuscript and printed versions of Petrarch's Epistolae Familiares were produced by analysing the paratextual elements that determine the order in which the letters are presented. The result is a proposal to modify and expand not only the material book itself, but also the significance and use of Petrarch’s collected letters, whether intended as spiritual and moral tracts or as a set of grammatical and rhetorical rules ("formulae”).
Keywords: Petrarca; Libri di lettere; Familiares; manoscritti; indicizzazione